Alignment of the Pixel and SCT Modules for the 2004 ATLAS Combined Test Beam - Ahmad, A; Andreazza, A; Atkinson, T; Baines, J; Barr, A; Beccherle, R; Bell, P; Bernabeu, J; Broklova, Z; de Renstrom, P; Cauz, D; Chevalier, L; et al. (2008)
A small set of final prototypes of the ATLAS Inner Detector silicon tracking system (Pixel Detector and SemiConductor Tracker), were used to take data during the 2004 Combined Test Beam. Data were collected from runs with beams of different flavour (electrons, pions, muons and photons) with a momentum range of 2 to 180 GeV/c. Four independent methods were used to align the silicon modules. The corrections obtained were validated using the known momenta of the beam particles and were shown to yield consistent results among the different alignment approaches. From the residual distributions, it is concluded that the precision attained in the alignment of the silicon modules is of the order of 5 μm in their most precise coordinate. © 2008 IOP Publishing Ltd and SISSA.